IMPLEMENTATION OF EDUCATIONAL TOURISM PROMOTION OF RUMAH JAMUR NANDO PEKANBARU - Tifany Apriliyasaci; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The tourism industry continues to grow along with the development of transportation and information technology which is marked by the increasing number of tourist destinations in each region. Educational tourism is a tourist activity while learning which aims to increase knowledge directly in a fun way. Educational Tourism Rumah Jamur Nando Pekanbaru is one of the educational tours that offers tours while learning about mushroom cultivation. To continue to increase visits to Rumah Jamur Nando, it is necessary to implement promotions. Therefore, this study aims to determine the Implementation of the Promotion of Educational Tourism of Rumah Jamur Nando Pekanbaru. The method used in this research is descriptive qualitative method. Based on the results of research through observation and interviews, the implementation of promotions carried out by the Rumah Jamur Nando is advertising, sales promotion, publicity and individual sales. Keywords: Tourism, Educational Tourism, Promotion Implementation.